The Listening Strategies of the Senior High School Students: An Overview (RETAIN, 2020)
Listening is counted as one of the crucial skills in language learning since listening involved with the language input and used to cooperate with other language skills. Many learners considered listening as the most challenging skill to be mastered. However, listening skills get the least attention from the teacher and the material’s instructional. Learners are rarely equipped with a strategy that can ease them to understand the listening input. Therefore, teachers need to support the students in finding a suitable strategy to help them to be better listeners. This article will deliver kinds of learners’ difficulties in their listening process and the use of listening strategy among senior high school students that assist them in overcoming their listening problems for becoming successful language learners. Some pedagogical implications also presented at the end of the article.